2018
DOI: 10.15195/v5.a11
|View full text |Cite
|
Sign up to set email alerts
|

Competition in the Family: Inequality between Siblings and the Intergenerational Transmission of Educational Advantage

Abstract: Research on educational mobility is concerned with inequalities between families. Differences in innate abilities and parental responses lead, however, to educational differences between siblings. If parental responses vary by family socioeconomic background, within-family inequality can affect between-family inequality (i.e., educational mobility). This study uses data from the German Socio-Economic Panel Study (SOEP) to test whether sibling similarity in education varies by family socioeconomic background. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 60 publications
(108 reference statements)
4
41
0
Order By: Relevance
“…With respect to variation in educational mobility across social groups, we found no evidence that sibling similarity in education varies by family socioeconomic background. Our findings are in line with previous research which found no such differences in Germany (Grätz 2018) and the United States (Conley 2008;Conley and Glauber 2008;Conley et al 2007). We replicate and expand these findings to a plurality of educational outcomes (cognitive skills, school grades, and final educational attainment) and societies (Finland, Germany, Norway, Sweden, the United Kingdom, and the United States).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…With respect to variation in educational mobility across social groups, we found no evidence that sibling similarity in education varies by family socioeconomic background. Our findings are in line with previous research which found no such differences in Germany (Grätz 2018) and the United States (Conley 2008;Conley and Glauber 2008;Conley et al 2007). We replicate and expand these findings to a plurality of educational outcomes (cognitive skills, school grades, and final educational attainment) and societies (Finland, Germany, Norway, Sweden, the United Kingdom, and the United States).…”
Section: Discussionsupporting
confidence: 92%
“…Evidence on the variation of sibling similarity by family socioeconomic background is mixed and results are so far limited to two countries. Previous research analyzing the variation of sibling 9 similarity between social groups in the United States (Conley 2008;Conley and Glauber 2008;Conley et al 2007) and Germany (Grätz 2018) found no variation in sibling similarity by family socioeconomic background with respect to cognitive skills and educational attainment. However, Conley and Glauber (2008) found higher levels of sibling resemblance in earnings and household income in the United States for siblings from socioeconomically advantaged families compared with siblings from socioeconomically disadvantaged families.…”
Section: Variation Of Universal Family Background Effects Across Socimentioning
confidence: 87%
See 2 more Smart Citations
“…We should state that respondents of the study were the Netherlands born between 1918 and 1974; therefore, the conclusions may not be fully sociologically relevant. The significance of birth order for a school success was researched also by Grätz (2018) in Germany. The author found that the presumed negative impact of birth order (as well as maternal age) on education is specific for socioeconomically disadvantaged families.…”
Section: Full Research Papermentioning
confidence: 99%